RELASI PATRONASE KIAI-SANTRI DALAM PENDIDIKAN KARAKTER DI PONDOK PESANTREN MA’HADUTHOLABAH BABAKAN TEGAL - Muhammad Misbah (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The relations of santri-kyai in pesantren (boarding school) brings out a high loyalty from santri to their Kyai. This is caused by figure of kyai who is generally perceived by society as a perfect person who emphasizes of virtuous behavior that emulated by his ummah. However, modernization has brought changes in all aspects of life including relations of kyai and santri at Pondok Pesantren Ma'hadutholabah Babakan Tegal. This study tries to elaborate relationship of kyai-santri in this pesantren, and its effects on santri’s character education. It uses in-depth interviews, documentation, observations, patronage data analysis, Islamic education, and character education theory. The results showed that the pattern of kyai-santri relationships in Pondok Pesantren Ma'hadutholabah can be included in the